The Impact of Natural Resource Discoveries in Latin America and the Caribbean : A Closer Look at the Case of Bolivia - Toscani, Frederik (IMF Working Papers; Working Paper ;, 2017)
This paper studies the impact of natural resource extraction in Latin America and the Caribbean (LAC) from a number of angles. First, we exploit a novel dataset on the universe of giant oil and gas discoveries in the region to trace out the cyclical response of macroeconomic variables to discoveries over the short- and medium-run. Second, we use non-stationary panel data techniques to look at the long-run (trend) relationship between GDP per capita and the value of oil and gas production-our results imply that the recent fall in prices could depress GDP per capita by several percentage points. Last, we use Bolivia, which discovered huge gas reserves in the late 1990s, as a case study to apply the cross-country results and to study the impact of discoveries at the subnational level.